Maria Montessori tra scienza spiritualità e laicità - Cives, Giacomo (Studi sulla Formazione/Open Journal of Education, 2015)
Has Maria Montessori an religious horizon? Yes, she have, but it’s laic and cosmic. It’s tied to her scientific education and to the cultural context in which she lived.